2017
DOI: 10.1126/scitranslmed.aaf6397
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of fecal microbiota from patients with irritable bowel syndrome alters gut function and behavior in recipient mice

Abstract: Irritable bowel syndrome (IBS) is a common disorder characterized by altered gut function and often is accompanied by comorbid anxiety. Although changes in the gut microbiota have been documented, their relevance to the clinical expression of IBS is unknown. To evaluate a functional role for commensal gut bacteria in IBS, we colonized germ-free mice with the fecal microbiota from healthy control individuals or IBS patients with diarrhea (IBS-D), with or without anxiety, and monitored gut function and behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
296
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 408 publications
(316 citation statements)
references
References 98 publications
14
296
0
6
Order By: Relevance
“…However, there is concern that more than desired microbes are being transmitted during FMT and that donors need to be carefully screened [125,126]. In one study, germ-free mice receiving fecal microbiota samples from patients with IBS-D exhibited increased GI transit, activation of innate immunity, and altered intestinal barrier function after 3 weeks compared with mice receiving fecal microbiota from healthy individuals [127]. Anxiety-like behavior was evident in mice receiving FMT from patients with IBS-D with anxiety, but not in mice receiving FMT from patients with IBS-D without anxiety or from healthy individuals.…”
Section: Fecal Microbiota Transplantationmentioning
confidence: 99%
“…However, there is concern that more than desired microbes are being transmitted during FMT and that donors need to be carefully screened [125,126]. In one study, germ-free mice receiving fecal microbiota samples from patients with IBS-D exhibited increased GI transit, activation of innate immunity, and altered intestinal barrier function after 3 weeks compared with mice receiving fecal microbiota from healthy individuals [127]. Anxiety-like behavior was evident in mice receiving FMT from patients with IBS-D with anxiety, but not in mice receiving FMT from patients with IBS-D without anxiety or from healthy individuals.…”
Section: Fecal Microbiota Transplantationmentioning
confidence: 99%
“…In a recent study, germ-free mice were colonized by fecal microbiota from 8 patients with diarrhea-predominant irritable bowel syndrome (IBS) and 5 healthy controls. 13 Fecal microbiota analysis of mice showed that it resembled the microbiota of the donor. Authors found that mice receiving microbiota from patients with IBS were more anxious (demonstrated by latency to step-down from the table and time spent in the light box) than those receiving microbiota from healthy subjects; 13 Intestinal transit, paracellular gut permeability, and the molecular markers of gut inflammation were also greater among the former group of mice.…”
mentioning
confidence: 99%
“…13 Fecal microbiota analysis of mice showed that it resembled the microbiota of the donor. Authors found that mice receiving microbiota from patients with IBS were more anxious (demonstrated by latency to step-down from the table and time spent in the light box) than those receiving microbiota from healthy subjects; 13 Intestinal transit, paracellular gut permeability, and the molecular markers of gut inflammation were also greater among the former group of mice. 13 Though the above-mentioned mechanistic studies are important in a scientific perspective, clinicians and patients are interested in knowing whether therapeutic interventions targeting the gut microbiota would have any clinically meaningful alteration in brain functions that may benefit the patients.…”
mentioning
confidence: 99%
“…A recent study by De Palma (1) has shown that fecal material from humans with irritable bowel syndrome (IBS) with diarrhea (IBS-D) invoked physical changes in the intestinal environment and in behavior. This is an interesting outcome, given the questions that have been raised about the relevance of certain models' in light of the differences between the rodent gut physiology, the microbiome and the human condition (2,3).…”
mentioning
confidence: 99%